Understanding supercapacitor performance: voltage dynamics and internal parameter calculations with validating experiments - Hassan, Mohd Khair; Che Soh, Azura; Abdul Rahman, Ribhan Zafira; Alsabari, Ali Mohsen (BP International, 2024)
Supercapacitors store electrical energy through the development of the double-layer capacitor structure at the interface between the anodes and the electrolyte. The modeling of the supercapacitor (SC) is crucial for its commercial application and can be represented by various models, including electrical, chemical, and electrochemical models. One of the models used to characterize the real-time operation characteristics of the supercapacitor is the equivalent circuit model. In addition to its mathematical complexity, the experiment's time-consuming nature poses a significant obstacle in acquiring the internal parameter values for the SC. The selection of test equipment, together with the experimental design structure, is a crucial factor that influences the correctness of the model. This project focuses on developing a systematic experimental strategy for SC (supercapacitor) modeling utilizing the Neware battery tester. The study describes and discusses the experimental procedure used to determine the internal properties of the SC. The experimental set-up was based on a Neware testing device with eight independent channels and an intermediate machine, host computer with the NEWARE software v7.5.6 and Matlab 2019a. The results were compared to an empirical model developed by earlier researchers. The terminal voltage of the superconductor (SC) was verified through experimentation, with a maximum relative inaccuracy of 0.045%. The proposed approach for parameter evaluation involves using two measurement points in the charge curve, as opposed to the four measurements typically utilized in the literature for both the charge and discharge phases. The model effectively replicates the dynamic behavior of the supercapacitor during the charge/discharge phase, demonstrating the accuracy of the suggested approach and model.